Salivary proteins as a biomarker for dental caries—A systematic review - Martins, Carla; Buczynski, Ana Karla; Maia, Lucianne Cople; Siqueira, Walter Luiz; Castro, Gloria Fernanda Barbosa de Araujo (Journal of dentistry, 2013)
To develop a systematic review based on the relation between salivary proteins and dental caries by comparing subjects with and without caries experience and to evaluate whether salivary proteins can be considered biomarkers for dental caries or not. An electronic search was performed in the PubMed Medline, Ovid Medline, ISI Web of Science, Medline, Cochrane Library, Lilacs, Scielo, BBO, Paho and Wholis databases applying the following MeSH terms: “dental caries” OR “tooth demineralization” OR “dental caries susceptibility” OR “dental enamel solubility” AND “salivary proteins and peptides” OR “saliva” AND “proteins”. To be eligible for the systematic review, the observational controlled studies had to have groups with and without caries experience. Studies with high risk of bias were excluded. From a total of 188 identified studies, only seven were included in this systematic review. Four studies were classified as “low risk of bias” and three as “moderate risk of bias”. Three studies reported a relation between salivary proteins and dental caries. There was not sufficient evidence to establish salivary proteins as a biomarker for this disease although three of the seven studies showed a relation between salivary proteins and dental caries in terms of protein phenotypes, total protein concentration and protein molecular weight.